Cancer patterns and trends in Central and South America. (September 2016) - Sierra, Mónica S.; Soerjomataram, Isabelle; Antoni, Sébastien; Laversanne, Mathieu; Piñeros, Marion; de Vries, Esther; Forman, David
Highlights: The leading incident cancers were prostate, lung, breast, cervix, colorectal, and stomach. These cancers were also the primary causes of cancer mortality. High/very high HDI countries experienced a high burden of prostate and breast cancer. Medium HDI countries had a high burden of stomach and cervical cancers. Resource-dependent interventions to prevent, diagnose, and treat cancer are urgently needed. Abstract: Rationale and objective: Cancer burden is increasing in Central and South America (CSA). We describe the current burden of cancer in CSA. Methods: We obtained regional and national-level cancer incidence data from 48 population-based registries (13 countries) and nation-wide cancer mortality data from the WHO (18 countries). We estimated world population age-standardized incidence and mortality rates per 100, 000 person-years. Results: The leading cancers diagnosed were prostate, lung, breast, cervix, colorectal, and stomach, which were also the primary causes of cancer mortality. Countries of high/very high human development index (HDI) in the region experienced a high burden of prostate and breast cancer while medium HDI countries had a high burden of stomach and cervical cancers. Between countries, incidence and mortality from all cancers combined varied by 2–3-fold. French Guyana, Brazil, Uruguay, and Argentina had the highest incidence of all cancers while Uruguay, Cuba, Argentina, and Chile had the highest mortality. Incidence of colorectum, prostate and thyroid cancers increased in Argentina, Brazil, Chile and Costa Rica from 1997 to 2008, while lung, stomach and cervical cancers decreased. Conclusion: CSA carries a double-burden of cancer, with elevated rates of infection- and lifestyle-related cancers. Encountered variation in cancer rates between countries may reflect differences in registration practices, healthcare access, and public awareness. Resource-dependent interventions to prevent, early diagnose, and treat cancer remain an urgent priority. There is an overwhelming need to improve the quality and coverage of cancer registration to guide and evaluate future cancer control policies and programs.